(untitled) (Aporte Santiaguino, 2024)
Global warming is causing the recession and alarming thinning of mountain glaciers worldwide; this carries the direct risk of glacial lake outburst floods (GLOF); triggering disasters such as landslides, which represent a significant threat to the safety of the population, local infrastructure and numerous losses of human life. Its objective was to compile findings between the years 2010 and 2023 from publications in accordance with the research method adopted, through a literature review consulting the Scopus, ScienceDirect and Researchgate databases. The methodology, taking into consideration the Prisma guidelines, the review process was segmented into four preliminary stages: identification, selection, evaluation and inclusion. The results of lake volume and area are well correlated R2 = 0.91, these data provide a clear vision regarding the methodologies for estimating the volume of lagoons. It was concluded that the investigations offer a deep insight into the methodologies over the years, they have improved their results, having accepted correlations, and in turn provide a solid basis for estimating volumes; There is an urgent need to strengthen integrated disaster risk management in mountainous regions.